ANALYSIS OF FACTORS AFFECTING THE AMOUNT OF COMMUNITY SAVINGS AT PT. BANK MANDIRI TBK - Oktavia Anna Rahayu (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this study was to analyze the influence of the BI rate and the inflation rate on the amount of savings at PT bank Mandiri, Tbk. In the last three years PT Bank Mandiri Tbk has been able to establish itself as the largest bank in Indonesia with quite large asset holdings according to the Finance Indonesia website. These assets are the result of raising funds from the public which are influenced by several factors, including inflation and interest rates. Therefore, the efforts that have been made so far need to be maintained and even increased so that the amount of funds raised by PT Bank Mandiri Tbk in the future will increase even more.Data collection techniques by searching data at Bank Mandiri and websites of data statistics centers. The analytical method used is the Multiple Linear Regression model. SPSS application is used to help test this model. The results of the study show that the BI rate and inflation rate have a significant effect on the amount of savings. The influence of the BI rate and the inflation rate on total savings is 89.1%.